2020
DOI: 10.3390/metabo10070269
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Analysis of Environmental Metabolomic Data in Ecotoxicology: Wild Marine Mussel Exposed to WWTP Effluent as a Case Study

Abstract: Environmental metabolomics is a powerful approach to investigate the response of organisms to contaminant exposure at a molecular scale. However, metabolomic responses to realistic environmental conditions can be hindered by factors intrinsic to the environment and the organism. Hence, a well-designed experimental exposure associated with adequate statistical analysis could be helpful to better characterize and relate the observed variability to its different origins. In the current study, we applied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Moreover, a significant alteration of neurohormones was observed, in particular a down-modulation of dopamine (−36%) and a serotonin metabolite 5-methoxyindoleacetate (−57%) levels. Dopamine and serotonin are both neurotransmitters regulating neuromuscular functions (valves closing, siphon activity, and ciliary movement) and, therefore, this study confirmed the neuromuscular and feeding behavior alterations that were observed in molluscs following exposure of contaminants, especially as pesticides, as previously described [ 158 ].…”
Section: Omics Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, a significant alteration of neurohormones was observed, in particular a down-modulation of dopamine (−36%) and a serotonin metabolite 5-methoxyindoleacetate (−57%) levels. Dopamine and serotonin are both neurotransmitters regulating neuromuscular functions (valves closing, siphon activity, and ciliary movement) and, therefore, this study confirmed the neuromuscular and feeding behavior alterations that were observed in molluscs following exposure of contaminants, especially as pesticides, as previously described [ 158 ].…”
Section: Omics Studiessupporting
confidence: 90%
“…A multifactorial analysis was applied to assess the metabolic response of mussel M. galloprovincialis exposed for seven days to a wastewater treatment plants (WWTP) effluent extract in laboratory conditions [ 158 ]. The WWTP was chemically characterized, identifying different organic contaminants, including drugs, chemotherapy drugs, stimulants (caffeine, nicotine), herbicides, and insecticides.…”
Section: Omics Studiesmentioning
confidence: 99%
“…Only a few metabolomic studies have explored sex-specific responses to a contaminant, although sex differences in response to contaminant exposure have been reported [ 38 , 47 , 48 ]. Such differences have already been highlighted in M. galloprovincialis when challenged by V. harveyi over a 24-h period [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prolonged exposure could trigger other MeOAs over time, or a contaminant might have several MeOAs [15]. Finally, regarding the organism under study, it is essential to inform the development stages (e.g., adult, larvae, and embryo) [42], as well as the sex [21,26,35,43], as the physiological and morphological differences could impact the MeOA (e.g., endocrine disruptors).…”
Section: Environmental Metabolomics To Decipher Mechanisms Of Action ...mentioning
confidence: 99%